The information-computing Internet-center «Aeromechanics». First line: the «Shock» program complex - Tarnavsky, G.A.; Tarnavsky, A.G.; Gilev, K.V. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2005)
The general architecture and the basic structure description of information-computing center «Aeromechanics» intended for distribution of scientific results in mathematical modeling of physical gas dynamics problems in the Internet-media are presented. For creation of scientific-commercial Web-site, the philosophy is worked out and the strategy is discussed. The tools of development, the tools of support of functioning, the role of design and content placement, and the marketing problems are considered. For drawing the visitors and ensuring a comfort of their visits to the Center, the main page and the second level pages are cited and their design and navigation are analyzed. The «Shock» program complex included in the Internet-center «Aeromechanics» as an independent structure (a branch of the communication graph) mdash; the first line of information-computing Web-resource mdash; is created. The pages of the site which realize the functions of this line: the main page, the bibliography page, the succession of processor system pages, the pages of tabular, and the graphical databases are considered.